Administration of Punong Barangays in the Implementation of Katarungang Pambarangay Law in the Province of Albay - Barcellano, Andres (JPAIR Multidisciplinary Research, 2025)
Republic Act 7160 or the Local Government Code of 1991 provides the Katarungang Pambarangay Law as an extra governmental mechanism aims at perpetuating the time-honoured tradition of amicably settling interpersonal disputes in a community without the recourse to the formal legal system. This study assess the administration of Punong Barangays in Katarungan Pambarangay Law. It specifically determined the profile of Punong Barangays and Lupong Tagapamayapa, assessed their administrative supervision along disposition of cases; timeliness; resolution of the cases; and communication and documentation and identified the key constraints encountered. This study conducted in the province of Albay, specifically in the city of Ligao, Tabaco and Legazpi covering the period from CY 2022 to 2024. This study used the Descriptive Quantitative Research Design. The respondents of the study are the selected Punong Barangays and Lupong Tagapamayapa. The study reveals that the Katarungang Pambarangay Law demonstrates consistently excellent performance in Albay, showcasing an effective local justice system that fosters community trust. However, significant knowledge gaps and practical challenges, including authority application and inter-barangay coordination, hinder the law’s effective implementation in Legazpi, Tabaco, and Ligao.